Stealing the game - Abdul-Jabbar, Kareem, 1947- (Abdul-Jabbar, Kareem, 1947- Streetball crew, 2015)
When eighth-grader Chris's older brother, Jax, is caught betting on the pick-up basketball games that Chris and his friends play, Chris becomes involved in the police investigation.